Quality of audit oversight in the context of the European Union - Monteiro, Daniela (2020)
Considering the entry into force of the new EU audit reform regarding statutory auditors, in effect in all member states since 2016, this research aims to identify which audit oversight rules are associated with a high level audit quality on both its dimensions, i.e., the actual quality and the perceived quality, in relation to Public Interest Entities, within the European Union, and whether those rules have the same impact on both dimensions. Its measurement was based on the following proxies: the quality of financial information through earnings management and the impact of qualified opinions on financial costs. The results do not corroborate all the choices made by the European Union in the new legal framework, as they do not lead to a positive association with audit quality and consolidate the assumption that the balance between competence and independence is not the only challenge related to the oversight of the audit profession. In particular, in relation to the transparency of the oversight process, we obtained an interesting and surprising result: more transparency is associated with a higher audit quality, as it constitutes an incentive to the auditor, given how it reflects on his reputation, but is also associated with a perceived low audit quality, which we interpret as an understanding that the audit performance is poor, instead of the audit oversight was effective. The evidence demonstrates that the balance between actual and perceived quality is a relevant matter. In conclusion, the real challenge is to identify the different aspects of the inverse effect between actual and perceived audit quality and how to keep them balanced, whilst ensuring the independence and competence of auditors